Design of Transition Mode Control System of Tilt-Wing UAV - RAMADHAN (NIM : 13113014), ARIEF
Tilt-Wing UAV (Unmanned Aerial Vehicle) is a type of aircraft which has wing that can be rotated. The tilt-wing mechanism is implemented to increase the performance of the aircraft. This aircraft is capable of doing vertical take-off and landing (VTOL) like a helicopter and flying horizontally like an airplane. This report will present the design of controller system of tilt-wing UAV. The design will be focused in the transition mode of the vehicle. Transition occurs between vertical flight and cruise flight and vice versa. The aircraft is controlled using PID controller. PID constants are tuned empirically. By observing the vehicle’s orientation data from the IMU (inertial Measurement Unit) sensor, vehicle’s stability can be detected. Based on the experiment, the PID constants responsible for a stable flight are, Kp = 0,5; Ki = 0,05; Kd = 0,01; for pitch and Kp = 2; Ki = 0,1; Kd = 0,01; for roll. These results hopefully will be useful in the developments of tilt-wing UAV.